WAYS OF DEVELOPING TEACHERS' COMPETENCIES IN WORKING WITH MODERN DIDACTIC RESOURCES - Milan, KLEMENT (Trends in education, 2015)
The current expansion of information and communication technology brings to the forefront of teachers modern, digital technology based didactic tools, using multimedia. The individual components of multimedia presentations that are mediated by demanding technical assemblies, dominated by IT, which alone is able to transfer information from various sources into a common environment by means of a process called digitization, have not only to be built, but also distributed to pupils, and shared with other members of teaching staff.All the above mentioned facts mean new challenges for teachers who have to be ready not only to use modern didactic resources and technologies, but also to create suitable teaching materials, and apply them in classes. The dynamically changing education paradigm thus places new demands on teachers who are not necessarily ICT experts, yet should be able to use the ICT tools in classes, acting primarily as advisors.The submitted paper presents the concept of training of the teaching staff of partner schools involved in the project Modern teacher (CZ.1.07/1.3.00/51.0041), which is financed by the European Social Fund and the state budget of the Czech Republic.
Keywords: information and communication technology; touch devices; innovation in education; modern teaching materials.